"It's the Method, Stupid." Interrelations between Methodological and Theoretical Advances: The Example of Comparing Higher Education Systems Internationally. (September 2017) - Hoelscher, Michael
This article argues that strong interrelations between methodological and theoretical advances exist. Progress in, especially comparative, methods may have important impacts on theory evaluation. By using the example of the "Varieties of Capitalism" approach and an international comparison of higher education systems, it can be shown that the use of improved data and of advanced analysis techniques changes the acceptance or rejection of the theoretical approach. As a conclusion, the article advocates data improvements, the use of advanced methods, more generally a methodologically reflexive interpretation of comparative research results as well as a closer cooperation between theory and method development.